Kültürel Miras Farkındalığı: Kastamonu Üniversitesi Turizm Fakültesi Öğrencileri Üzerine Bir Araştırma - Yaşarsoy, Emrah; Koç, Dilara Eylül; Ulema, Şevki (Turk Turizm Arastirmalari Dergisi, 2021)
This research was carried out in order to determine the cultural heritage awareness of Kastamonu students and to increase this awareness. The research is designed to solve two interrelated problems. First of all, the current awareness levels of the students were tried to be measured. Then, how to increase the points where the students' level of awareness could be increased constituted the scope of the research. The questionnaire technique was used in this quantitatively designed research. The questionnaire forms were implemented electronically to 230 participants who were determined with convenience sampling method and voluntary approach. The data obtained from the research were analyzed with SPSS 22.0 and MAXQDA. As a result of the research, it was determined that the cultural heritage awareness of the participants was generally high. In particular, it was specified that the "Ataturk and Serife Baci Monument", "Kastamonu Castle" and "Clock Tower" are among the most well-known places. As a result of the comparison tests applied, it was determined that cultural heritage awareness did not differ according to the genders and departments of the participants, but significant differences were found between age groups. The participants emphasized that promotion activities should be carried out effectively for the development of tourism in Kastamonu, it is extremely important to increase various festival-style activities, the infrastructure and superstructure works should be accelerated and it is essential to make new investments.